Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
The solution to the system of equations using elimination method is (1, 1, 0)
Given the system of equations;
-2x+2y+3z=0 ............. 1
-2x-y+z=-3 .............2
2x+3y+3z=5 ...............3
Subtracting 1 from 2 will give;
2y+y + 3z-z = 0-(-3)
3y + 2z = 3 ...................... 4
Add equation 2 and 3
-y + 3y + z + 3z = -3 + 5
2y+4z = 2
y+2z = 1 .............. 5
Solve 4 and 5 simultaneously:
3y + 2z = 3 .......... 4
y+2z = 1 .............. 5
Subtract 4 from 5 to have:
3y - y = 3 - 1
2y = 2
y = 1
Since y + 2z = 1
1 + 2z = 1
2z = 0
z = 0
Substitute y = 1 and z = 0 into the equation 2:
Recall from 2;
-2x - y + z = -3
-2x - 1 = -3
-2x = -3 + 1
-2x = -2
x = 1
Hence the solution to the system of equations is (1, 1, 0)
Learn more here: https://brainly.com/question/15165519
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.